Identification and Characterization of Phytochemicals and Polyphenolic Compounds in Ethylacetate Fraction of Desmodium velutinum (Wild.) DC. Methanol Root Extract Using High-performance Liquid Chromatography (HPLC): Ethylacetate Fraction of D. velutinum Methanol Root (Biological Sciences - PJSIR, 2024)
This present study evaluated the phytochemical and bioactive constituents of Desmodium velutinum root. This was carried out using standard methods and HPLC. The extraction of 1000 g of Desmodium velutinum root with methanol (80%) produced an extract with a percentage yield of 3.45%. The fractionation of 40 g of Desmodium velutinum root methanol extract using ethylacetate gave a percentage yield of 15%. Results of the quantitative phytochemical analysis showed alkaloids (6.82 ± 2.31 mg/g), flavonoids (1.03 ± 0.01 mg/g), tannins (3.82 ± 0.03 mg/g) and phenols (5.12 ± 0.06 mg/g), while saponin and steroids were not detected. The high performance liquid chromatography analysis of the ethylacetate fraction of Desmodium velutinum root methanol extract showed the concentration of various constituents of flavonoids, phenols and tannins. The flavonoids include chlorogenic acid (0.6052 µg/g), catechin (1.1424 µg/g), rutin hydrate (0.1253 µg/g), caffeic acid (0.1725 µg/g), quercetin (0.3689 µg/g) and an unidentified flavonoid compound with retention time, 0.065 min. The phenols identified were ascorbic acid  (0.1482µg/g), p-coumaric acid (0.0174 µg/g), rutin (0.0205 µg/g), ferulic acid (0.5782 µg/g), apigenin  (0.2344µg/g) and an unidentified phenolic compound with retention time, 15.907 min, while the tannins identified were ellagitannin (0.2214 µg/g) and gallotannin (0.1396 µg/g) as well as eight (8) unidentified tannic compounds with different retention time. This study reveals that ethyl acetate fraction of Desmodium velutinum methanol root extract contains bioactive compounds and this validate its possible option as therapeutic agent or drug formulation, as it could aid in the prevention and alleviation of cancer, ulcer and other health complications.